Aksi Kekerasan Atas Nama Agama - Abdul Jalil (Andragogi: Jurnal Diklat Teknis Pendidikan dan Keagamaan, 2021)
[VIOLENCE IN THE NAME OF RELIGION: A STUDY OF FUNDAMENTALISM, RADICALISM, AND EXTREMISM] This paper will examine fundamentalism, radicalism, and extremism based on a historical view to examine the root of the problem. The method used in this paper is a qualitative descriptive approach through historical-critical studies. The expected output of this study is an informative contribution so that it can put the right paradigm in viewing acts of violence with religious nuances. The terms fundamentalism and radicalism in the Western perspective are often associated with extreme attitudes, old-fashioned, stagnation, conservative, anti-Western, and hard to defend opinions, even with physical violence. The use of the term radicalism or fundamentalism for Muslims is not appropriate, because the radicalism movement is very contrary to Islamic teachings. The symptom of violent practices carried out by a group of Muslims, historically-sociologically, is more appropriate as a socio-political symptom than a religious phenomenon, even though they are waving religious banners. Terrorism is the anti-climax of extreme tendencies in views and attitudes.